2000
DOI: 10.1021/bm005525y
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Description of the Gelation Mechanism of Konjac Mannan

Abstract: A molecular level description of the time course of the gelation of the polysaccharide konjac mannan (KM) is presented and the role of alkali addition is considered in detail. NMR relaxometry is utilized as a complementary methodology to mechanical spectroscopy in order to probe events occurring as a prelude to network formation, and high-resolution NMR is used to follow the deactetylation process. It is shown that the addition of alkali plays an important solubilizing role in addition to facilitating the deac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(52 citation statements)
references
References 37 publications
5
45
0
2
Order By: Relevance
“…In other words, the changes of rheological behaviors with pH and temperature can be associated with alternation of other molecular properties than deacetylation. The findings are in agreement with the view of Williams et al (2000) that gelation of native KGM solution may also occur without deacetylation.…”
Section: Infrared Spectral Characteristicssupporting
confidence: 92%
See 2 more Smart Citations
“…In other words, the changes of rheological behaviors with pH and temperature can be associated with alternation of other molecular properties than deacetylation. The findings are in agreement with the view of Williams et al (2000) that gelation of native KGM solution may also occur without deacetylation.…”
Section: Infrared Spectral Characteristicssupporting
confidence: 92%
“…Similar to the changes observed from the above IR and Raman spectra of KGM, deacetylation has also occurred to KGM as a result of combined alkaline and heat treatment in previous studies Solo-de-Zaldivar et al, 2014;Williams et al, 2000). Deacetylation in KGM could significantly affect its solubility and gelling properties (Du, Li, Chen, & Li, 2012).…”
Section: Infrared Spectral Characteristicssupporting
confidence: 81%
See 1 more Smart Citation
“…The results generally showed higher cohesiveness values when using alkaline solution compared with sodium alginate. This may due to the loss of acetyl groups from KGM chains by adding alkaline solution, called deacetylation [16][17][18][19][20][21]. The effects of eliminating acetyl groups produced junction zones through hydrogen bonding between calcium ions and deacetylated anions (R-CH 2 O -), between water molecules and hydroxyl groups (OH -) of deacetylated KGM, and by van der Waals, charge transfer and hydrophobic interactions, forming a strong, elastic, and thermally stable gel network structure [11,22,23] to provide high springiness and cohesiveness of samples.…”
Section: Production Of Konjac Noodlesmentioning
confidence: 99%
“…In alkaline solution, Harrington and Morris (2009) observed the appearance of deacetylation and gel network structure of KGM (Harrington & Morris, 2009). Furthermore, Williams et al (2000) researched the deacetylation and aggregation kinetics, the results showed that the alkali played the role of deacetylation and solubilization, and the deacetylation reduced the solubility and negated the alkali-induced polyelectrolytic nature on the polysaccharide chain (Williams et al, 2000). In addition, Goycoolea, Morris, and Gidley (1995) and Doyle, Lyons, and Morris (2009) proved that the alkali could destroyed the intermolecular association (hyperentanglement), which had the effects of ionization and introduction of negative charge along the polymer chains, and the electrostatic repulsion resulted in the reduction of viscosity, however, by addition of salt, the screening effect gave rise to the increases of viscosity (Doyle et al, 2009;Goycoolea et al, 1995).…”
Section: Introductionmentioning
confidence: 99%